Spin filter effect of hBN/Co detector electrodes in a 3D topological insulator spin valve. (16th February 2018) - Vaklinova, Kristina; Polyudov, Katharina; Burghard, Marko; Kern, Klaus
Abstract: Topological insulators emerge as promising components of spintronic devices, in particular for applications where all-electrical spin control is essential. While the capability of these materials to generate spin-polarized currents is well established, only very little is known about the spin injection/extraction into/out of them. Here, we explore the switching behavior of lateral spin valves comprising the 3D topological insulator Bi2 Te2 Se as channel, which is separated from ferromagnetic Cobalt detector contacts by an ultrathin hexagonal boron nitride (hBN) tunnel barrier. The corresponding contact resistance displays a notable variation, which is correlated with a change of the switching characteristics of the spin valve. For contact resistances below ~5 kΩ, the hysteresis in the switching curve reverses upon reversing the applied current, as expected for spin-polarized currents carried by the helical surface states. By contrast, for higher contact resistances an opposite polarity of the hysteresis loop is observed, which is independent of the current direction, a behavior signifying negative spin detection efficiency of the multilayer hBN/Co contacts combined with bias-induced spin signal inversion. Our findings suggest the possibility to tune the spin exchange across the interface between a ferromagnetic metal and a topological insulator through the number of intervening hBN layers.